2012
DOI: 10.5339/connect.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and seasonal variation of phytoplankton community in the Santragachi Lake, West Bengal, India

Abstract: The study of phytoplankton diversity and its seasonal variation was carried out by sampling water taken from the Santragachi Lake, of West Bengal between November 2009 and July 2010. Various physico-chemical variables were recorded and the correlation of this with phytoplankton density was established using Canonical Correspondence Analysis. This showed that the density of phytoplankton was higher when temperature and nutrients were increased. A total of 29 phytoplankton taxa belonging to Chlorophyta (10), Cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
5
27
1
Order By: Relevance
“…This conformed to the studies made by Paramasivam and Srinivasan (1981), Maeda et al (1992), Kumari et al (2008), Ghosh et al (2012). Rain water might have brought more nutrients into the lake as surface run off which enhanced the growth of phytoplankton especially Cyanobacteria and Euglenophyceae.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This conformed to the studies made by Paramasivam and Srinivasan (1981), Maeda et al (1992), Kumari et al (2008), Ghosh et al (2012). Rain water might have brought more nutrients into the lake as surface run off which enhanced the growth of phytoplankton especially Cyanobacteria and Euglenophyceae.…”
Section: Discussionsupporting
confidence: 53%
“…etc. as shown by Swarnalatha and Narasingrao (1993) and Ghosh et al (2012). Ceratium hirundinella was also recorded in another oxbow lake of Cachar District (Das et al, 2011).…”
Section: Discussionmentioning
confidence: 71%
“…Marshall and Alden (1990) also concluded that salinity gradients in estuaries were more important than variation in nutrient concentrations in determining the composition of phytoplankton communities. This is however not always the case especially in freshwater dominated estuaries and lakes such as the Nyara Estuary (Walker et al, 2001) and Sundays Estuary (Kotsedi et al, 2012) in South Africa, or the Santragachi lake in, India (Ghosh et al, 2012), where phytoplankton community structure and blooms were mainly due to high nutrient concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses have been successfully used to analyse the changes in biological communities and the physicochemical variables in polluted sites (Aguilera et al 2006;Bernal et al 2008;Ghosh et al 2012). Principal component analysis (PCA) is a wellrecognized multivariate statistical tool that can be applied in the ecotoxicological monitoring programs to investigate differences between the variables.…”
Section: Discussionmentioning
confidence: 99%